Comparative outcomes of DSAEK and DMEK in eyes with prior Ahmed glaucoma valve implantation - Do-Hyeon An; Gyeongmin Yoo; Ji-Yun Song; Jin-Uk Beak; So-Hyang Chung; Hyun-Seung Kim; Yong-Soo Byun (PLoS ONE, 2026)
Background To compare the outcomes of Descemet stripping automated endothelial keratoplasty (DSAEK) and Descemet membrane endothelial keratoplasty (DMEK) in eyes with prior Ahmed glaucoma valve (AGV) implantation. Methods This retrospective study included 27 eyes from 27 patients who underwent endothelial keratoplasty (16 DSAEK, 11 DMEK) between 01/01/2020 and 31/12/2022. All eyes had a prior AGV implantation and a minimum follow-up of 12 months. Best-corrected visual acuity (BCVA), endothelial cell density (ECD), central corneal thickness (CCT), complications, and graft survival were compared between groups. Results The donor age was significantly younger in the DSAEK group (52.94 ± 11.17 years vs. 62.36 ± 10.02 years, P = 0.034). The DSAEK group had significantly higher ECD at 6 and 12 months (1583.2 ± 562.6 and 1441.1 ± 502.6 cells/mm²) compared to the DMEK group (1109.5 ± 484.8 and 1046.6 ± 327.3 cells/mm², P = 0.040 and P = 0.043). However, this difference was no longer significant after covariate analysis with donor ECD. Postoperative BCVA improved significantly in both groups, with no significant differences between them. Complication rates were comparable. The 1-year survival rates were 87% for DSAEK and 91% for DMEK, the 2-year survival rates were 78% for DSAEK and 74% for DMEK. Mean graft survival was 28.7 ± 3.3 months for DSAEK and 24.7 ± 2.8 months for DMEK (P = 0.777). Conclusions DSAEK and DMEK demonstrated comparable visual outcomes, complication rates, and graft survival in eyes with prior AGV implantation. While both procedures appear to be viable options for this complex patient population, these findings should be confirmed in larger studies.